TIAGO SINIBALDI, ESCHATOLOGY AND REDEMPTION (Journal of Teleological Science, 2022)
We assume three criteria to evaluate Sinibaldi's thought in its broad outlines. First, the central theme of the metaphysics of St. Thomas Aquinas: the discovery of being as act, intensive act of all beings and the consequent real distinction between being and essence in beings: "Ipsum esse est perfectissimum omnium, comparatur enim ad omnia ut actus". Let's see what Sinibaldi thinks. In the treatise on Ontology, which is the second treatise of his Elements, we find the term existence instead of being and that the aforementioned distinction of Thomas is reported as a real distinction essence and existence. This is the attitude that can be characterized as essentialism. Secondly, the criterion that the loss of the Thomistic originality of being belongs to school Thomism and this has important effects not only in philosophy but also in theology. Third, relationship between spirituality and philosophical-theological speculation.
Keywords: James Sinibaldi; Redemption; Eschatology